Disclosing bad news of cancer: patients’ preference for communication - Saqib , Sabah Uddin; Khawaja Muhammad Inam Pal (Journal of the Pakistan Medical Association, 2021)
Introduction: The majority of cancer patients’ relatives in developing countries, especially in Pakistan prefers and demand, and in most times impose a “do not tell approach”, while counselling for patients disease. Thus, the aim of the current study is to first assess patients’ understanding about his or her disease and see preferences regarding the manner in which physicians’ deliver news about cancer diagnosis and its management plan. Material and methods: This was a cross-sectional qualitative study. Patients were approached and interviewed while having their regular follow-up. An immediate relative of the patient was also included in the study to see family perception regarding disease after their consent. This study enrolled 55 patients with 6 different types of cancers. Results: This study shows that 35 (65.5%) patients did not know stage at diagnosis while 40 (72.7%) patients did not know the current stage of their disease. In 22 (40%) cases, patient’s family knew diagnosis ahead of patient and 19 (86.3%) families asked clinicians to hide diagnosis news from the patient. This study demonstrates, specialist oncologist for breaking news, family counseling, helping patient to figure out how to tell diagnosis to others, telling news directly to the patient and the effects of cancer on daily life are preferred area to communicate on first visit. Conclusion: Disclosing cancer news is always an unfavorable experience not only for patient and family but also clinician as well. In our population both patient understanding and communication demands improvements. Continuous...